2012
DOI: 10.1016/j.apsusc.2012.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Study of the nitridation process of TiSi2 powder

Abstract: This paper reports on the nitriding process of TiSi 2 micro/submicrometer-sized powders. TiSi 2 powders were treated under nitrogen flow, at 1100°C, during various durations. The composition and morphology of the nitride powders are characterized by X-ray diffraction and observed on cross-section, prepared using ion polishing system by scanning electron microscopy whereas the chemical composition is analyzed by energy dispersive X-ray spectroscopy. All these analyses revealed that under nitrogen flow, TiSi 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It is attributed to the transformation of TiSi 2 into free silicon and TiN according the Equation 1 (partial nitridation), into the surface and inside the grains. The mass gain corresponds to around 14 % that is expected [22] .…”
Section: 1a Commercial Tisi 2 Powdermentioning
confidence: 70%
See 1 more Smart Citation
“…It is attributed to the transformation of TiSi 2 into free silicon and TiN according the Equation 1 (partial nitridation), into the surface and inside the grains. The mass gain corresponds to around 14 % that is expected [22] .…”
Section: 1a Commercial Tisi 2 Powdermentioning
confidence: 70%
“…Under nitrogen atmosphere, the nitridation of TiSi 2 starts around 1000°C, and leads to the formation of TiN (d = 5.43 g/cm 3 ) and Si 3 N 4 (d = 3.19 g/cm 3 ) with a 57 volume percent increase when the reaction is complete. It is well-known that the powder size can influence the reaction rate; therefore several studies were performed to prepare ceramic composites with a small size powder obtained by ball-milling [20][21][22] . To control the process, the nitridation of TiSi 2 must be well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This observation shows that the powder is impregnated into the inter-bundle macropores. The TiSi 2 nitridation created TiN, Si 3 N 4 and free Si phases [23] . Preforms used were consolidated with the resin A, therefore it is not always possible to determine if the observed ceramic residue is the results of the consolidation by the final PIP cycle.…”
Section: Characterizations Of Compositesmentioning
confidence: 99%
“…As it has been suggested by P. Greil in the case of ceramic preparation, this problem could be overcome with the use of active fillers, which react during pyrolysis under reactive atmosphere to form oxides, carbides or nitrides leading to a significant volume expansion that can decrease the matrix porosity [11][12][13][14][15][16][17][18][19][20] . Among various expansion agents, titanium disilicide powder (TiSi 2 ) is identified as an interesting active filler [20][21][22][23] . Under nitrogen atmosphere, the nitridation of sub-micronic TiSi 2 powder starts around 1000°C, and leads to the formation of TiN (d = 5.43 g/cm 3 ) and Si 3 N 4 (d = 3.19 g/cm 3 ) with a large volume increase even if the reaction is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of composite can be easily obtained by self-propagating high temperature synthesis (SHS) under nitrogen atmosphere [17]. Previous studies undertaken on the nitridation of TiSi 2 powders demonstrated that the nitridation of this compound is a two stepped mechanism [18][19][20]. The influence of the temperature factor was also reported with a noticeable acceleration of the kinetics above 1100°C.…”
Section: Introductionmentioning
confidence: 99%